Diversifikasi Pengolahan Frozen Nugget, Pengemasan dan Pemasaran Google Bisnis - Zaki, Irham; Herianingrum, Sri; Hapsari, Meri Indri; Bayuny, Ahmad Fadlur Rahman; Wijayanti, Ida (Jurnal Ilmiah Pengabdian dan Inovasi, 2024)
The Covid 19 pandemic which has spread throughout the world has had a very bad impact on the national economy, including the rural economy. Because economic activity in urban areas has stopped, production demand in rural areas has also been affected. By using ABCD (Asset-Based Community Development) approach, the objective of this community service is to increase the productivity and economy of Sugihwaras village residents by using several methods. The first is to increase the diversification of existing products while increasing the value of goods sold by the community. Second, increase citizens' marketing level to the next level by providing an understanding of online marketing. The third is to increase the community's basic financial understanding with financial management and basic accounting counseling. The results of the community service program showed that there was a very significant increase in the understanding of the participants on the materials that had been taught.